A Pink Writing Experiment - Löytönen, Teija; Koro-Ljungberg, Mirka; Carlson, David; Orange, Amy; Cruz, Joshua (Reconceptualizing Educational Research Methodology, 2015)
This article addresses a collaborative writing experiment that explores spaces of diverse encounters that began at a research conference held in the Flamingo hotel in Las Vegas; spaces where knowings emerge in the (shared) moment, in-between (our)selves, prompted by different (research) questions and entanglements of matter and meaning. Through these multiple and emergent writing encounters we explore ways towards collaborative scholarly writing and accessible ways of working and knowing beyond the immediately known or sensed. In addition, this collaborative writing experiment serves to inspire and engage participants (qualitative researchers and ethnographers alike) to explore, share, and disseminate knowledge across contexts differently. We call for writing in qualitative research that senses, figures out, and “reveals” via moving and sensuous bodies, and emerging embodied encounters within particular spaces.